2020
DOI: 10.1088/1742-6596/1511/1/012029
|View full text |Cite
|
Sign up to set email alerts
|

Identification of preservice biology teachers’ metacognitive awareness and metacognitive skills

Abstract: Metacognition can make a significant contribution to learning, especially that related to intellectual ability. Students’ metacognitive awareness and skills can be developed through consistent implementation of appropriate learning designs and students’ progress monitoring. The current research attempted to identify students’ metacognitive awareness and metacognitive skills in a biology education context. This research involved 142 preservice biology teachers from STKIP Pembangunan Indonesia Makassar, UIN Alau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 10 publications
0
5
0
1
Order By: Relevance
“…Thus far, students have become accustomed to the lecturing method and learning instructions delivered primarily by the lecturer, which has an effect on students' learning autonomy. The lack of variety in the use of supportive learning models results in a lack of self-confidence and self-confidence of students in class (Amin, 2022;Amin & Adiansyah, 2020). Meanwhile, in traditional learning, students are more passive and less motivated to learn because the lecturer directly imparts information.…”
Section: Finding and Discussionmentioning
confidence: 99%
“…Thus far, students have become accustomed to the lecturing method and learning instructions delivered primarily by the lecturer, which has an effect on students' learning autonomy. The lack of variety in the use of supportive learning models results in a lack of self-confidence and self-confidence of students in class (Amin, 2022;Amin & Adiansyah, 2020). Meanwhile, in traditional learning, students are more passive and less motivated to learn because the lecturer directly imparts information.…”
Section: Finding and Discussionmentioning
confidence: 99%
“…Aspek berpikir tingkat tinggi menjadi hal penting dalam menyiapkan peserta didik menjadi pebelajar yang mampu memecahkan masalah (Amin & Adiansyah, 2020;Retnawati et al, 2018).…”
Section: Hasilunclassified
“…The rubric included eight measures (0-7), which were used to evaluate students' responses to each test item. According to Green [49], the levels of metacognitive skills are as: "super (85-100), ok (68-84), development (51)(52)(53)(54)(55)(56)(57)(58)(59)(60)(61)(62)(63)(64)(65)(66)(67), cannot really (34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50), risk (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)…”
Section: Data Collectionmentioning
confidence: 99%
“…The studies found a substantial relationship between students' metacognitive skills and retention [1], [32]- [34]. Additionally, it was discovered that students' metacognitive skills correlated positively with the improvement of their learning outcomes [35]. Research results related to metacognitive skills and scientific attitudes in Indonesia's learning process are still relatively low.…”
mentioning
confidence: 99%